Incidência de atores privados e de processos de privatização na política educacional do estado da Paraíba - Moura, Sergio Andrade de (2022)
The privatization of education is a complex and multifaceted phenomenon that is happening globally in the context of the hegemony of neoliberalism, the New Public Management oriented state reforms, and the free-market agenda for education. As well, it is the result of intense action by multiple actors in policy networks, at various levels, dimensions, and contexts, in the face of a paradigmatic change in the relationships between governments, the new philanthropy, and the market. Privatization of education occurs through the use of multiple strategies and policy technologies in educational reforms, inspired by market “solutions” and “best practices” that promote a reconfiguration of the public education sector under the discursive arguments of achieving greater efficiency and supposedly better “quality” (BALL; YOUDELL, 2007; BALL, 2014; VERGER, FONTDEVILA, ZANCAJO, 2017). In this scenario, the objective of this thesis is to analyze, in the context of the New Public Management reforms of the last decade, the incidence of private actors and the strategies employed in the privatization processes of education in the Paraíba state school system. For that, the research was developed using the literature review and the survey and documental analysis referring to the investigated object. In addition, it uses the Policy Cycle Approach (BOWE; BALL; GOLD, 1992) as a theoretical and methodological reference and is anchored on the analytical key presented by Ball and Youdell (2008) that categorizes the privatization of public education in two fundamental ways: endogenous and exogenous. As a result of this study, there was an accentuated role of private actors in public education in Paraíba. The evidence showed, in the first place, that private actors entered into public-private partnerships with the state of Paraíba, mobilized human, financial and material resources, and, as experts, carried out consultations, provided materials, promoted the training of teachers and managers, proposed “solutions” and transferred pedagogical and management models inspired by technologies and private management standards, provided services through the use of management contracts and so on. Moreover, they participated in the formulation, planning, and decision-making processes of educational policies, together with governors, policy makers, and civil servants, in a coordinated, interconnected, and interdependent structure that is characteristic of heterarchical governance. The evidence indicated, second, the occurrence of an educational reform process, explicitly articulated with the new forms of power and state management, which employed several strategies and policy technologies inscribed in the scope of the managerial rationality of the New Public Management, such as large-scale standardized evaluations, adoption of centrally defined learning objectives and standards, contractualization of explicit goals, emphasis on accountability, stimulus to competition and to the constitution of quasi-markets, as well as of meritocracy through the payment of financial bonuses linked to individual performance, among others. Throughout this process, the boundaries between public and private became blurred, education was reconfigured according to the standards of the New Public Management and privatization in and of education was promoted in the education network of the state of Paraíba.